(untitled) (Semiárida, 2020)
In this contribution the whole genera and species of the VeroensC6B9 family which grows spontaneously in the Province of La Pampa, Argentine, are Iisted. This family is represented by10 genera with 29 species. Keys for the identification of the genera and species are included. A short description, the synonymy, the popular names, distribution and diffusion in La Pampa, and the studied exemplars, of each specie is given.